An evaluation of bush fire prevention and control policy in Ghana - Ashon, Edward Kweku (2011)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the degree of Master of Science in Development Policy Planning.